Geología de los cuadrángulos de Cunambo, Mariscal Cáceres, Río Pucaruro, Vargas Guerra, Río Huitoyacu, Checherta, Andoas, Lamastipishca, San Antonio, Nuevo Soplín, Valencia, Pucaruro, Sungache, Puncuna, Villa Trompeteros, San Fernando, San Juan de Pavayacu, Río Urituyacu, Santa Martha, Barranca, San Isidro, Río Nucuray y Urarinas 5-k, 5-l,5-m, 6-h, 6-i, 6-j, 6-k, 6-l, 6-m, 7-k, 7-l, 7-m, 8-k, 8-l, 8-m, 9-j, 9-k, 9-l, 9-m, 10-j, 10-k, 10-l, 10-m – [Boletín A 130] - Quispesivana Quispe, Luis Juan (1999)
211 p., 23 mapas